The Act of Killing - Oppenheimer, Joshua (Denmark : Sørensen, Signe Byrge, 2012)
Throughout the thirty-one years of General Suharto’s military-backed government, the country sanitized its bloody history through an official narrative that glorified its 1965-66 purges, which saw around one million alleged Communists murdered by bloodthirsty militias. In 1965, Anwar and his friends were promoted from small-time gangsters selling movie theatre tickets on the black market to death squad leaders. In less than a year, they helped the army kill over one million alleged Communists, ethnic Chinese, and intellectuals. Anwar and his friends have not been forced by history to admit they participated in crimes against humanity. Instead, they have written their own triumphant history, becoming role models for millions of young paramilitaries. The Act of Killing is a journey into the memories and imaginations of the perpetrators, offering an insight into the minds of mass killers. It is a nightmarish vision of a frighteningly banal culture of impunity in which killers can joke about crimes against humanity on television chat shows, and celebrate moral disaster with the ease and grace of a soft shoe dance number.
Verzio Film Festival Submission
Verzio Film Festival Submission